Assessment The Knowledge Of Nursing College Students' Concerning Corona Virus Infection (Covid19) (Journal of Pharmaceutical Negative Results, 2023)
Background: The study was designed for the assessment of the knowledge of nursing students regarding pandemics. In the current designed study, the level of awareness was checked and the majority of students were found aware of SARS-CoV and SARS-Cov2 (Covid-19).Objective: To assess the awareness of SARS-CoV and SARS-Cov2 (Covid-19) among nursing students of Karbala college.Subjects and Methods: A cross-sectional survey was carried out in different universities of Karbala in 2021. A self-constructed questionnaire by Pursuing the clinical and community administration of COVID-19 given by the National Health Commission of the People's Republic of China was used among the 120 students who are enrolled in different nursing universities of Karbala and SPSS version 23 was used to analyze the data.Results: The majority (n=65, 54.1%) were male, (n=49, 40.8%) having age between 21to 23years and (n=83, 69.1%) were unmarried. In educational status (n=30, 36%) were undergraduate with education type in governmental university (n=48) Aware answer. During the assessment of awareness towards Covid-19 results showed that (n=80, 66.66%) were aware regarding Covid19.Conclusion: This study finalized that the students enrolled in different nursing universities of Karbala were aware of the Covid19. The observed awareness can be due to qualitative education especially in the domain of disease prevention, which has beenprovided by the educational institutions of Karbala in collaboration with the Ministry of Health. Keywords: Awareness, Covid-19, nursing students.